EFEKTIVITAS DM LEARNING MENGGUNAKAN APLIKASI TERHADAP TINGKAT KECEMASAN PASIEN DIABETES MELLITUS DI POLIKLINIK RUMAH SAKIT - Evi Wahyuni; Wigyo Susanto; Dwi Heppy Rochmawati (Journal Healthcare Education, 2026)
Diabetes mellitus (DM) patients can experience anxiety due to complex disease management, fear of complications (kidney failure, amputation), the impact of lifestyle changes, and lack of social support. DM Learning can help DM patients manage their disease, where DM learning is an educational tool about DM disease that includes an understanding of the causes, symptoms, treatment methods (diet, exercise, medication), complications, and prevention, so that sufferers and the general public can manage DM effectively and improve their quality of life. Objective: This study aimed to determine the effectiveness of DM Learning using an application on the anxiety level of DM patients at the Sari Asih Serang Hospital Polyclinic. Method: A quasi-experimental study with a pretest–posttest design with a control group. Each group consisted of 60 respondents taken using a purposive sampling technique. Data were analyzed univariately and bivariately using the marginal homogeneity test. Results: The analysis results showed that application-based DM learning was effective in reducing the anxiety level of diabetes mellitus patients (p: 0.000). Conventional DM learning was also effective in reducing the anxiety level of diabetes mellitus patients (p: 0.000). Application-based DM learning is more effective in reducing anxiety levels in diabetes mellitus patients compared to conventional DM learning (p: 0.000). Conclusion: Application-based DM learning is effective in reducing anxiety levels in diabetes mellitus patients.